ENHANCING STUDENTS' ENGLISH PRONUNCIATION THROUGH CAKE APPLICATION - Deliani, Thia Wulan (Universitas Borneo Tarakan, 2023)
The researcher who was taking part in this study was putting a strong emphasis on pronunciation and application as the primary areas of investigation. This was carried out to enhance the student's capacity to acquire an accent. This study used both an experimental technique and a quasi-experimental configuration to develop its research structure. Each of these approaches was used in conjunction with the other. Participants in this study were categorized into two independent groups: the control group and the experimental group. Both groups were responsible for carrying out the research experiment. There was no difference between the obligations that were given to both of the groups. It was revealed through the data processes that enhancing the pronunciation skill using cake application has a beneficial impact on the studentsâ€™ English pronunciation studentsâ€™ level.Â